Fragmentasi Manusia dalam Kultur Makan Masa Kini - Susilo, Ferdy (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2015)
Food has been one of the most important foundations of human history. Food functions as a statement of the self, a classification system, a way of social interaction, and even a cultural identity that it can be interpreted holistically. Food has been one of the most important elements that shape life and the history of human civilization. It demonstrates a kind of culture that signifies the dynamic of humanity from one era to the other. The expansion of food industry has brought a great impact on the revolution of social interaction model. However, a reduction of the food value is happening nowadays throughout the food culture, seeing it as simply as nutrition and economical commodity. Hedonism triggers the view of food as a tool to conquer the human desire, which actually never ceased even after being satisfied. A sort of ‘McDonaldization’ system is considered as a grand system of living that might have significantly changed many aspects of human life in this globalisation era. The Branded Life propaganda of the food industry seems to mislead people to continue their luxurious life. The fragmentation of human’s views on food becomes one of its consequences and in turn changes human’s respect of food within its holistic picture. The discussion now covers the social and spiritual dimensions. Today, the fragmented views of food have turned into a threat to humanity, but also a great opportunity, notwithstanding uncomfortable, to highlight the missing aspects of food in the midst of contemporary culture.